Peregrinações por terras estranhas: a representação da guerra indígena em viagens helenísticas de franceses: André Thevet e Jean de Léry - Soares Neta, Maria Angelina (2011)
This work aims to show the importance of traveler s reports, in the construction of a speech referring to the Pagan Greek society as a reference to the Christian understanding of otherness tupinambá. Thus, the image of tupinambá will be analyzed, and compared to the warriors of antiquity, passing on to the construction sites of the Indian war from models of other pagan universes related to the Christianity European family of five hundred. We will address the operation of travel literature as a model of writing, to speak of the unknown. The representations of war from their canons in the traditions of ancient epic and historiography will be analyzed, considering it with examples of Hellenism from five hundred.